Prognostic evaluation of preoperative systemic immune inflammatory index in patients with colorectal cancer - Zhang, Tao; Miao, Yong chang (Frontiers in Oncology, 2023)
Objective To investigate the impact of preoperative systemic immune inflammatory index (SII) on the clinical prognosis of patients undergoing colorectal cancer (CRC) surgery. Methods One hundred and sixty CRC patients who underwent surgical treatment in our gastrointestinal surgery department from January 2019 to May 2023 were collected. ROC curves were applied to determine the sensitivity and specificity of SII, determine the optimal cut-off value into low SII and high SII groups, compare the clinicopathological data of SII patients in the two groups, and analyze the postoperative survival of patients in the two groups using Kaplan-Meier and Log-rank methods. Univariate and multifactor COX proportional risk regression models were used to analyze clinical prognostic factors. Results The ROC curve showed that the area under the curve of SII for the evaluation of OS in CRC patients was 0.859, and the best cut-off value was 513.53. There was statistical significance (P < 0.05) in terms of tissue grading and diabetes mellitus in both groups. The Kaplan-Meier survival curves showed that the overall survival rates of the SII<513.53 group and the SII≥513.53 group were 50.88% (29/57) and 32.04% (33/103), and the overall survival rate of the SII<513.53 group was significantly higher than that of the SII≥513.53 group, and the difference was statistically significance (χ2 = 8.375, P=0.004). COX proportional risk regression showed that TNM stage, lymph node metastases, anastomotic fistula and SII were independent risk factors affecting postoperative survival in patients with CRC. Conclusion Preoperative SII is an independent prognostic factor for CRC, which is simple, convenient, and non-invasive, and can be used to predict the prognosis of CRC patients.